Shedding light on the shadows: Transparency challenge in background life cycle inventory data - Jing Guo; Ruiqiao Li; Ruirui Zhang; Jianchuan Qi; Nan Li; Changqing Xu; Anthony S. F. Chiu; Yutao Wang; Hiroki Tanikawa; Ming Xu (Journal of Industrial Ecology, 2025)
Life cycle assessment (LCA) hinges on the transparency and reliability of inventory data. However, the transparency of background life cycle inventory (LCI) data sources remains unexamined. This research assesses data transparency in mainstream LCI databases using a two‐step examination system based on source findability and accessibility. Six major databases (ecoinvent, GaBi, U.S. Life Cycle Inventory Database, European Life Cycle Database, Inventory Database for Environmental Analysis, and Chinese Life Cycle Database) were analyzed by sampling processes and tracing their sources. The results reveal widespread transparency issues, with only 40%–60% of sampled processes having findable sources and <5% being fully accessible in certain databases. Incomplete documentation and complex cross‐referencing between processes and sources posed key barriers. The lack of transparency undermines LCA credibility and necessitates reconstructing databases for enhanced traceability. Although a preliminary study, these findings highlight the challenge of data transparency and provide a methodology to evaluate databases. This drives collective action to uphold transparency standards, restoring trust in LCA as a sustainability decision‐making tool.